ALAT UKUR GRAVITAS BUMI MENGGUNAKAN METODE GERAK JATUH BEBAS - -, M. Fakhri (Universitas Pasir Pengaraian, 2015)
During this time we prove the magnitude of the acceleration of the Earth'sgravity using a pendulum swing that require data that is more complex and requiresreasoning is quite high because with this method we associate the acceleration of gravity with aligned vibrations. In the study the authors designed a measuringinstrument with the Earth's gravitational acceleration using a digital stopwatch. With this method we associate with the Earth's gravitational acceleration of free fall motion that can be watched instantly. Thus obtained can be that the earth's acceleration due to gravity (g) = 9.845 at Pasir Putih Pasirpengarayan, standard deviation (S) = 1.25 and Volume and mass of the object in general (of the whole experiment) did not affect the acceleration of Earth's gravity, but in terms of the deviation alleged state of the air at the time could affect the acceleration of gravity.